DIAGNOSIS OF NON-ALCOHOLIC FATTY LIVER DISEASE AND ITS PREVENTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, opinions were expressed about the diagnosis of non-alcoholic fatty liver disease and its prevention.